A WHO Reference Reagent for lupus (anti-dsDNA) antibodies: international collaborative study to evaluate a candidate preparation. Issue 12 (5th September 2019) - Fox, Bernard J; Hockley, Jason; Rigsby, Peter; Dolman, Carl; Meroni, Pier Luigi; Rönnelid, Johan
Abstract : Introduction: Antibodies against double-stranded DNA (anti-dsDNA) are a specific biomarker for systemic lupus erythematosus (SLE). The first WHO International Standard (IS) for anti-dsDNA (established in 1985), which was used to assign units to diagnostic tests, was exhausted over a decade ago. Methods: Plasma from a patient with SLE was first evaluated in 42 European laboratories. The plasma was thereafter used by the National Institute for Biological Standards and Control to prepare a candidate WHO reference preparation for lupus (anti-dsDNA) antibodies. That preparation, coded 15/174, was subjected to an international collaborative study, including 36 laboratories from 17 countries. Results: The plasma mainly contained anti-dsDNA, other anti-chromatin antibodies and anti-Ku. The international collaborative study showed that the field would benefit from 15/174 as a common reference reagent improving differences in performance between different assays. However, no statistically meaningful overall potency or assay parallelism and commutability could be shown. Conclusion: 15/174 cannot be considered equivalent to the first IS for anti-dsDNA (Wo/80) and was established as a WHO Reference Reagent for lupus (oligo-specific) anti-dsDNA antibodies with a nominal value of 100 units/ampoule. This preparation is intended to be used to align test methods quantifying levels of anti-dsDNA antibodies.